Comparison of VHH‐Fc antibody production in Arabidopsis thaliana, Nicotiana benthamiana and Pichia pastoris. Issue 7 (30th January 2015) - De Meyer, Thomas; Laukens, Bram; Nolf, Jonah; Van Lerberge, Els; De Rycke, Riet; De Beuckelaer, Ans; De Buck, Sylvie; Callewaert, Nico; Depicker, Ann
Summary VHHs or nanobodies are widely acknowledged as interesting diagnostic and therapeutic tools. However, for some applications, multivalent antibody formats, such as the dimeric VHH‐Fc format, are desired to increase the functional affinity. The scope of this study was to compare transient expression of diagnostic VHH‐Fc antibodies in Nicotiana benthamiana leaves with their stable expression in Arabidopsis thaliana seeds and Pichia pastoris. To this end, VHH‐Fc antibodies targeting green fluorescent protein or the A. thaliana seed storage proteins (albumin and globulin) were produced in the three platforms. Differences were mainly observed in the accumulation levels and glycosylation patterns. Interestingly, although in plants oligomannosidic N‐glycans were expected for KDEL‐tagged VHH‐Fcs, several VHH‐Fcs with an intact KDEL‐tag carried complex‐type N‐glycans, suggesting a dysfunctional retention in the endoplasmic reticulum. All VHH‐Fcs were equally functional across expression platforms and several outperformed their corresponding VHH in terms of sensitivity in ELISA.